ELABORASI DAN EKSPLORASI PEMAHAMAN FIKIH KONTEMPORER - Mustafa, Muhtadin Dg. (Hunafa: Jurnal Studia Islamika, 2008)
This article elaborates the probelms of undersatanding the material of Islamic learning popularly known as fiqh, which is regarded less dinamical and less responsive to the change of time. Therefore, fiqh is very important to discuss since nowadys it is faced with the methodology of its implementation, that its infiteness between legal dictum having been formulated by claasical Muslim scholars with condition and legal probelms of their own as well as justice sense of Muslim society where the law was implemented. Wthin this context, a methodology of implementing fiqh is crucial to study in accordance with the change of room and of time.Kata Kunci: pemahaman fikih, hukum Islam, Alquran, sunah, ijtihad